Intracellular and Plasma Trough Concentration and Pharmacogenetics of Telaprevir - Jessica Cusato; Sarah Allegra; Amedeo De Nicolò; Lucio Boglione; Giovanna Fatiguso; Adnan Mohamed Abdi; Giuseppe Cariti; Giovanni Di Perri; Antonio D'Avolio (Frontiers Media S.A., 2015)
PURPOSE: Triple therapy for HCV-1 infection consists in boceprevir or telaprevir, ribavirin and PEG-interferon. Telaprevir is a P-glycoprotein substrate and it is metabolized by CYP3A4/5. No data have been published on intracellular penetration of telaprevir. We determined peripheral blood mononuclear cells (PBMCs) and trough plasma S and R telaprevir isomers concentrations; moreover, we evaluated the influence of some single nucleotide polymorphisms (SNPs) on these pharmacokinetic data after 1 month of triple therapy in humans. METHODS: Plasma and intracellular telaprevir concentrations were determined at the end of dosing interval (Ctrough) using ULPC-MS/MS validated methods; allelic discrimination was performed through real-time PCR. RESULTS: Median telaprevir Ctrough plasma concentrations were 2579 ng/mL and 2233 ng/mL for the pharmacologically more active S, and R, enantiomers, respectively, with median S/R plasma ratio of 1.11. In PBMC, the medians were 6863 ng/mL and 1096 ng/mL for S and R, respectively, with median S/R being 5.73. The PBMC:plasma ratio for S was 2.59 for R. Plasma ribavirin concentrations were directly correlated with plasma S-telaprevir concentrations. In linear regression analysis, only CYP24A1_rs2585428 SNP (p=0.003) and body mass index (p=0.038) were able to predict S-telaprevir PBMC concentrations. CONCLUSIONS: Our preliminary data could increase the understanding of mechanisms underlying telaprevir intracellular and plasma exposure, suggesting the implementation of pharmacogenetics in these drug kinetic studies.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.